Standards of Knowledge and the Rationality of Action - Grobler, Adam (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
In the paper Pragmatic Encroachment is contested. Classical Bank Case is reassessed in terms of the distinction between knowledge and prediction made upon that knowledge and the ceteris paribus clause involved. It is demonstrated that knowledge relevant for the prediction in question cannot provide the subject with the probability estimates of predictions that are necessary for making a rational choice. In other cases, the rise of stakes is sometimes accompanied with epistemic reasons to suspend the relevant ceteris paribus clause. Finally, some cautious self-denials may be questionable and motivated by the considerations independent of stakes. In conclusion it is claimed that, instead of the plausibility of knowledge-ascription, it is how knowledge is applied to the choice of action that depends on the stakes.